Poliandri dalam Perspektif Pancasila dan Hukum Islam: Kajian Konstitusional dan Nilai-Nilai Kebangsaan: Polyandry in the Perspective of Pancasila and Islamic Law: Constitutional Studies and National Values - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Marsha Cahya Shakilla; Nur Amalina; Aini Zulaika; Isna Maziyah Agustin (Litera Academica Publishing, 2024)
The phenomenon of polyandry in Indonesia has given rise to debate regarding individual rights and freedom in choosing a partner, which has begun to be advocated by some community groups in the context of human rights. However, this practice is not recognized in Indonesian positive law and is considered inconsistent with the values ​​of Pancasila, especially the principles of